Quantifying Bacterial Chemotaxis in Controlled and Stationary Chemical Gradients with a Microfluidic Device - Adam Gargasson; Carine Douarche; Peter Mergaert; Harold Auradou (Bio-Protocol)
Chemotaxis refers to the ability of organisms to detect chemical gradients and bias their motion accordingly. Quantifying this bias is critical for many applications and requires a device that can generate and maintain a constant concentration field over a long period allowing for the observation of bacterial responses. In 2010, a method was introduced that combines microfluidics and hydrogel to facilitate the diffusion of chemical species and to set a linear gradient in a bacterial suspension in the absence of liquid flow. The device consists of three closely parallel channels, with the two outermost channels containing chemical species at varying concentrations, forming a uniform, stationary, and controlled gradient between them. Bacteria positioned in the central channel respond to this gradient by accumulating toward the high chemoattractant concentrations. Video-imaging of bacteria in fluorescent microscopy followed by trajectory analysis provide access to the key diffusive and chemotactic parameters of motility for the studied bacterial species. This technique offers a significant advantage over other microfluidic techniques as it enables observations in a stationary gradient. Here, we outline a modified and improved protocol that allows for the renewal of the bacterial population, modification of the chemical environment, and the performance of new measurements using the same chip. To demonstrate its efficacy, the protocol was used to measure the response of a strain of Escherichia coli to gradients of α-methyl-aspartate across the entire response range of the bacteria and for different gradients.